EFFECT OF BAP (6-BENZYLAMINOPURINE) ON SHOOT INDUCTION IN EXPLANTS OF BRAZILWOOD - Aragão, Ana Katarina Oliveira (2015)
The Brazilian Atlantic forest has been subjected to intense degradation, with only about 7% to 8% of its original area remaining today. This situation has raised concerns over the conservation of species threatened with extinction. In all, 276 tree and bush species are under threat, out of which this study chose to evaluate alternatives for protecting brazilwood ‘Pau-Brasil’ (Caesalpinia echinata Lam.). Most studies performed so far on this subject either evaluate the effect of cytokinins on induction of callogenesis or focus on improving cryopreservation methodologies. In an attempt to expand knowledge about biotechnological techniques enabling conservation of C. echinata, this work evaluated the effect of 6-benzylaminopurine (BAP) and explant type on induction of shoots in brazilwood. To attain that, explants were inoculated into basic MS medium and into MS medium supplemented with 2.5 μM, 3.5 μM and 4.5 μM of BAP, and kept in a growth room for 40 days under controlled photoperiod and temperature conditions. A 2x4 factorial design was adopted, with three replicates. Analyzed variables included shoot percentage, callogenesis and oxidations, and means were compared by the Tukey test at the 5% probability level. Results showed a signifi cant infl uence of BAP only on shoot induction, and of explant type on that variable and on other variables too. It was concluded that, under in vitro conditions, the nodal type of explant is more responsive to BAP action and that 2.5 μM is the recommended concentration for shoot induction in brazilwood.